2018
DOI: 10.1093/ons/opy213
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Optical Contrast of Skull Base Tumors During Endoscopic Endonasal Surgery

Abstract: In this preliminary study of a small set of patients, we demonstrate that second-window ICG can provide NIR optical tumor contrast in 3 types of ventral skull-base tumors. Chordomas demonstrated the weakest NIR signal, suggesting limited utility in those patients. Both nonfunctional and functional pituitary adenomas appear to accumulate ICG, but utility for margin detection for the adenomas is limited by low specificity. Craniopharyngiomas with third ventricular extension appear to be a particularly promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This study and subsequent reports in skull base tumors found that Gd enhancement on T1-weighted MRI was the strongest predictor of positive fluorescence, whereas nonenhancing tumors did not fluoresce, providing insight into the mechanism of ICG localization. 7,16 In 2012, Ergin et al had proposed using intravenous ICG injections to optically monitor blood-brain barrier (BBB) disruption, taking advantage of the same EPR effect proposed to underpin ICG accumulation in the tumor microenvironment. 17 In the initial SWIG study from 2016, findings in patients with contrast-enhancing gliomas (12/15) were used to calculate diagnostic test characteristics.…”
Section: Clinical Trials Of Icg For Fluorescence-guided Intracranial mentioning
confidence: 99%
See 1 more Smart Citation
“…This study and subsequent reports in skull base tumors found that Gd enhancement on T1-weighted MRI was the strongest predictor of positive fluorescence, whereas nonenhancing tumors did not fluoresce, providing insight into the mechanism of ICG localization. 7,16 In 2012, Ergin et al had proposed using intravenous ICG injections to optically monitor blood-brain barrier (BBB) disruption, taking advantage of the same EPR effect proposed to underpin ICG accumulation in the tumor microenvironment. 17 In the initial SWIG study from 2016, findings in patients with contrast-enhancing gliomas (12/15) were used to calculate diagnostic test characteristics.…”
Section: Clinical Trials Of Icg For Fluorescence-guided Intracranial mentioning
confidence: 99%
“…Other studies have demonstrated ICG's ability to visualize chordoma, craniopharyngioma, pineocytoma, and intraventricular tumors. 16,22,23 Because the ultimate goal of FGS is to maximize extent of resection, studies by Cho et al in 2020 24 and Teng et al 76 comparing NIR fluorescence to the gold standard postoperative MRI showed that the absence of re- sidual NIR signal postresection closely correlated to GTR of HGGs (p < 0.0001) and intracranial metastases (p = 0.007) on MRI. One limitation of these findings, however, is intrinsic to the SWIG technique itself.…”
Section: Clinical Trials Of Icg For Fluorescence-guided Intracranial mentioning
confidence: 99%
“…Finally, SWIG is applicable to skull base tumors, such as pituitary adenomas, chordomas, and craniopharyngiomas, which were accessed via the transnasal/transsphenoidal approach. A 2018 study of 8 pituitary adenomas, 3 craniopharyngiomas, and 4 chordomas demonstrated that all the tumors demonstrated NIR fluorescence ( Figure 6 ) ( 53 ). Again, contrast-enhancement on preoperative MRI was the best predictor of NIR fluorescence contrast to normal background ( p -value = 0.0003).…”
Section: Evidence and Potential Benefits Of Swigmentioning
confidence: 99%
“…Patients with chordomas (top row), craniopharyngiomas (middle row), and pituitary adenomas (bottom row) all demonstrate NIR fluorescence with SWIG. Visualization was performed with a NIR-sensitive endoscope system ( 53 ).…”
Section: Evidence and Potential Benefits Of Swigmentioning
confidence: 99%
“…26 This approach has allowed neurosurgeons to visualize fluorescence confined to the neoplastic tissue of HGG, meningiomas, metastases, and pituitary adenomas with surprisingly high signal-to-background ratios. [27][28][29][30][31][32] Indeed, the visualization of abnormal tissue is very similar to principles of gadolinium contrast-enhancement in MRI, which relies on passive diffusion of contrast agent into abnormal tumor tissue with permeable vascular endothelium. Since gadolinium enhancement is the very basis of the definition of gross total resection or partial resection of glioma in surgical outcome studies for glioblastoma, SWIG TumorGlow™ has the potential to help neurosurgeons increase the extent of resection in HGG resections.…”
Section: Tumorglow™ For Adult Brain Tumorsmentioning
confidence: 98%